Phenomenon Childfree in Abdul Mustaqim's Maqashidi Interpretation - Supranggono, Zerlinda Prasanti; Nahdliyah , Siti Naila; Yardho , Moh (Jaanur Elbarik Indonesia, 2025)
This research uses a qualitative approach with a literature study. Primary data sources refer to Abdul Mustaqim's thoughts on the Maqashidi Tafsir methodology and Qur'anic verses related to offspring ( hifdz al- nasl ), while secondary data are obtained from sociological, psychological, and demographic literature. The analysis is conducted thematically and content-wise using the ushul al- khamsah framework to assess the benefits and harms of the childfree option. The research findings show that, from the perspective of Maqashidi Tafsir, the childfree phenomenon cannot be judged in a black-and-white manner. Although Islam generally emphasizes hifdz al- nasl (protecting offspring), the principle of hifdz al- nafs (protecting the soul) can be a top priority if the presence of a child is predicted to cause medical or psychological harm (such as severe trauma/violence). The Maqashidi approach offers flexible yet responsible legal solutions by distinguishing between universal principles ( kulliyyat ) and individual cases ( juz'iyyat ).